Association between pelvic floor muscle trauma and pelvic organ prolapse 20 years after delivery. Issue 1 (January 2016) - Volløyhaug, Ingrid; Mørkved, Siv; Salvesen, Kjell
Abstract Introduction and hypothesis It is known that pelvic floor muscle trauma (PFMT) after vaginal delivery is associated with pelvic organ prolapse (POP) symptoms (sPOP) and signs (POP-Q ≥2) in patient populations. Our aims were to establish the prevalence and investigate a possible association between PFMT and sPOP and POP-Q ≥2 in healthy women 20 years after their first delivery. Methods During 2013 and 2014 we conducted a cross-sectional study among 847 women who delivered their first child between 1990 and 1997. Women responded to a postal questionnaire and were offered a clinical examination including prolapse grading and pelvic floor ultrasonography. The main outcome measures were sPOP, POP-Q ≥2 and PFMT, defined by levator avulsion or a levator hiatal area on Valsalva manoeuvre of >40 cm2 on ultrasonography. Results Of the 847 eligible women, 608 (72 %) were examined. Data on POP symptoms, POP-Q stage, levator avulsion and levator hiatal area were available in 598, 608, 606 and 554 women, respectively, and of these 75 (13 %) had sPOP, 275 (45 %) had POP-Q ≥2, 113 (19 %) had levator avulsion and 164 (30 %) had a levator hiatal area >40 cm2 . Levator avulsion was associated with POP-Q ≥2 with an odds ratio (OR) of 9.91 and a 95 % confidence interval (CI) of 5.73 – 17.13, and with sPOP (OR 2.28, 95 % CI 1.34 – 3.91). Levator hiatal area >40 cm2 was associated with POP-Q ≥2 (OR 6.98, 95 % CI 4.54,  – 10.74) and sPOP (OR 3.28, 95 % CI 1.96 – 5.50). Conclusion Many healthy women selected from the general population have symptoms and signs of POP 20 years after their first delivery, and PFMT is associated with POP-Q ≥2 and sPOP.